An enhanced bioindicator for calorimetric monitoring of prophage‐activating chemicals in the trace concentration range. Issue 7 (1st June 2018) - Xu, Juan; Jiang, Feng‐Lei; Liu, Yi; Kiesel, Bärbel; Maskow, Thomas
Abstract: Viruses that infect bacteria (bacteriophages) can either lyse bacteria directly or integrate their genome into the bacterial genome. In the latter case, the viral genome (called prophage) remains dormant, and both phages and bacteria are able to survive in this state. But the silent prophages can be reactivated by, e.g., chemicals, accompanied by the release of substantial quantities of phage particles that further infect other phage‐sensitive bacteria, thus harming ecosystems or technical systems by way of a viral bloom. Recently, a calorimetric method was developed to monitor the prophage‐activating properties of chemicals. The method evaluates the difference in the metabolic heat of the Escherichia coli bioindicator with (λ+) and without (λ−) lambda prophages under the influence of the test substances. Simulations and experiments clearly demonstrate that the sensitivity of the test can be significantly improved, when a customized mixture of λ+ and λ− E. coli strains is used for enhanced bioindication. Hence, the new method mirrors a common situation in nature, where bacteria with and without prophages coexist. In summary, a monitoring method is suggested that provides quick results (after few hours) and offers both the option for automation with low workload (requires only a few minutes) and usage of commercially available instruments.